Antiviral nanoparticles for sanitizing surfaces: A roadmap to self-sterilizing against COVID-19. (October 2021) - Lin, Neil; Verma, Daksh; Saini, Nikhil; Arbi, Ramis; Munir, Muhammad; Jovic, Marko; Turak, Ayse
Highlights: Metal-based nanoparticles exert a diverse range of inactivation mechanisms, limiting the development of viral resistance. Antiviral mechanisms include oxidative damage and binding protein inhibition to effectively disable a broad range of viruses. Nanoparticles can be integrated into materials such as polymers and gels to confer sterilizing properties. The efficacy of nanoparticles for inactivating structurally similar viruses demonstrates potential for inhibiting SARS-CoV-2. Graphical Abstract: ga1 Abstract: Nanoparticles provide new opportunities in merging therapeutics and new materials, with current research efforts just beginning to scratch the surface of their diverse benefits and potential applications. One such application, the use of inorganic nanoparticles in antiseptic coatings to prevent pathogen transmission and infection, has seen promising developments. Notably, the high reactive surface area to volume ratio and unique chemical properties of metal-based nanoparticles enables their potent inactivation of viruses. Nanoparticles exert their virucidal action through mechanisms including inhibition of virus-cell receptor binding, reactive oxygen species oxidation and destructive displacement bonding with key viral structures. The prevention of viral outbreaks is one of the foremost challenges to medical science today, emphasizing the importance of research efforts to develop nanoparticles for preventative antiviral applications. In this review, the use of nanoparticles to inactivate other viruses, such as influenza, HIV-1, or norovirus, among others, will be discussed to extrapolate broad-spectrum antiviral mechanisms that could also inhibit SARS-CoV-2 pathogenesis. This review analyzes the published literature to highlight the current state of knowledge regarding the efficacy of metal-based nanoparticles and other antiviral materials for biomedical, sterile polymer, and surface coating applications.